A first principles investigation of lithium intercalation in TiO2-B - Panduwinata, Dwi; Gale, Julian (The Royal Society of Chemistry, 2009)
The intercalation of lithium into the polymorph of titania, TiO2-B, has been examined using firstprinciples methods, based on the Generalized Gradient Approximation within density functionaltheory. Three symmetry unique sites have been identified for the preferential location of lithium withinthe structure at low concentration, as well as the diffusion pathways between these sites. Lithium isfound to bind most favourably at a site close to the titania octahedral layer, while the lowest activationenergy for diffusion of 27 kJ mol-1 is found for diffusion along the open channel parallel to the b axis ofthe material. The need to activate lithium towards diffusion through the population of higher energybinding sites within the channel, along with the larger barrier for lithium to migrate through thesidewalls of nanotubular TiO2-B, provides an explanation for many of the observed experimentalelectrochemical properties of this potential battery material.